Plasma enhanced magnetic nano composite photocatalyst with memory catalysis effect, preparation method and application

By depositing NaYF4:Yb,Tm@TiO2/Fe3O4 nanocomposites with Au, the problems of low light utilization, difficult recycling and high energy consumption in photocatalytic technology were solved, and efficient degradation and convenient recycling of organic pollutants under discontinuous lighting conditions were achieved.

CN120733761APending Publication Date: 2025-10-03TIANJIN MEDICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510789511.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-13
Publication Date
2025-10-03

AI Technical Summary

Technical Problem

Existing photocatalytic technology has problems such as low light utilization, difficult recovery, high energy consumption and insufficient catalytic efficiency when treating azo dyes and ciprofloxacin in water, especially under discontinuous lighting conditions.

Method used

Au-deposited NaYF4:Yb,Tm@TiO2/Fe3O4 nanocomposite materials are used, combining upconversion, surface plasmon resonance and magnetic separation characteristics. The spectral response is broadened by NaYF4:Yb,Tm upconversion nanoparticles, Au nanoparticles capture and store photogenerated electrons, and Fe3O4 provides magnetic recovery capabilities to achieve a memory catalytic effect.

Benefits of technology

It can efficiently degrade organic pollutants in water under natural light, has full-spectrum response capabilities, and can continue to catalyze after the light stops, realizing convenient recycling of nanomaterials, with high degradation efficiency and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120733761A_ABST
    Figure CN120733761A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of environmental photocatalytic environmental governance, and particularly relates to a plasma enhanced magnetic nano composite photocatalyst with a memory catalysis effect, a preparation method and application, and the nano composite photocatalyst is a NaYF4: Yb, Tm-coated TiO2 / Fe3O4 core-shell structure nano composite material deposited by plasma enhanced magnetic Au. According to the nano composite photocatalyst, TiO2 is used as a matrix, and efficient conversion from visible light to ultraviolet light is realized by coating NaYF4: Yb, Tm up-conversion nanoparticles capable of being excited by near-infrared light; fe3O4 is compounded to endow the material with magnetic recovery performance; au nano-particles deposited on the surface of the core shell enhance the surface plasma effect and carrier separation, and the photocatalytic activity is further improved. The plasma enhanced magnetic nano-composite photocatalyst with the memory catalysis effect can efficiently degrade organic pollutants under the illumination condition, can perform continuous catalytic degradation after illumination is stopped, and provides a breakthrough technical path for solving the problem of sustainable degradation of the current photocatalysis technology under the complex environment condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of environmental photocatalysis and environmental governance, and in particular relates to a plasma-enhanced magnetic nanocomposite photocatalyst with a memory catalytic effect, a preparation method and an application thereof. Background Art

[0002] The global water environment is currently facing an increasingly serious challenge of organic pollution, with large amounts of environmentally persistent organic pollutants being continuously discharged into the aquatic environment. Among the many pollution sources, the textile printing and dyeing industry is particularly prominent. The production of wet fabrics involves different stages such as printing, dyeing and finishing, and requires the use of excessive amounts of water (120-280 liters) and various dyes to complete this process. Azo dyes, as the largest group of colorants, account for 70% of all organic dyes produced in the world. They are produced from coal and petroleum intermediates, with an annual output of approximately 7x10 5 Tons. These nitrogen-containing dye pollutants (such as malachite green and rhodamine B) have two notable environmental characteristics: First, they are highly persistent. Due to the stable benzene ring and azo bond in their molecular structure, they can persist in the natural environment for decades and are difficult to eliminate through natural degradation. Second, they are hazardous. Many azo dyes, their reduced degradation products, and chemically related aromatic amines have been reported to affect human health, causing skin irritation, allergies, headaches, and congenital malformations.

[0003] At the same time, more emerging pollutants with potential risks have been discovered. These substances include pharmaceuticals and personal care products (PPCPs), endocrine disruptors (EDCs), antibiotics, etc. The environmental concentrations are usually in the ng / L-μg / L range, but they may cause more significant ecological risks. Among them, fluoroquinolone antibiotics, as a typical emerging pollutant, not only have direct toxic effects on aquatic organisms, but also induce microorganisms to produce antibiotic resistance genes through long-term low-dose exposure. Ciprofloxacin, as a typical representative of the third-generation fluoroquinolone antibiotics, contains piperazine rings and fluorine atoms in its molecular structure, which constitutes extremely strong chemical stability. The half-life is as long as 150-180 days, leading to continuous accumulation in the aquatic environment. In addition, ciprofloxacin can induce Escherichia coli to produce drug-resistant mutations at low concentrations. This strong inducibility makes ciprofloxacin an important driving force for the spread of antibiotic resistance genes in the environment. When dyes and antibiotics coexist in the environment, they form a complex pollution system with a synergistic enhancement effect: the dye molecules act as photosensitizers to promote the photochemical transformation of antibiotics, producing more toxic derivatives; while the antibiotics significantly slow the biodegradation of the dyes by inhibiting the metabolic activity of microorganisms. This complex pollution not only increases the ecological toxicity of water several times but also, through exposure pathways such as drinking water and the food chain, causes multiple health hazards in humans, including endocrine disruption, increased carcinogenicity, and clinical drug failure. Faced with this severe situation, the development of efficient degradation technologies for azo dyes and ciprofloxacin is not only related to conventional pollution control but also a key link in curbing the spread of antibiotic-resistant genes.

[0004] At present, existing technologies for the removal of dyes and antibiotics from wastewater still face many challenges. The presence of antibiotics will significantly inhibit microbial activity, promote the enrichment of antibiotic-resistant bacteria in sewage treatment systems, and significantly reduce the efficiency of traditional physical and chemical biological treatment technologies. In order to overcome these problems, it is necessary to find more effective sewage treatment methods. Advanced oxidation technology (AOPs), as an emerging water pollution control method, has received widespread attention in the field of wastewater pollutant removal. Among them, photocatalytic oxidation technology has become a very promising type of AOPs due to its high efficiency, low toxicity and environmental friendliness, showing broad application prospects. This technology converts the absorbed solar energy into chemical energy through photovoltaic conversion, thereby driving a series of chemical reactions. The core of this process is that when the semiconductor photocatalyst is excited by energy photons exceeding its band gap, the photogenerated carriers participate in the redox process of water (H2O) and molecular oxygen (O2) on the catalyst surface, and ultimately generate hydroxyl radicals (·OH) and superoxide anions (·O2 - ) and other reactive oxygen species (ROS). These ROS are key contributors to photocatalytic activity, capable of decomposing various pollutants and ultimately mineralizing them into carbon dioxide and water.

[0005] In recent years, various nanosemiconductors, including titanium dioxide (TiO2), zinc oxide (ZnO), and cuprous oxide (CuO), have been widely used in photocatalytic degradation. TiO2, a widely popular n-type semiconductor, is considered a promising multiphase semiconductor photocatalytic material due to its environmental inertness, high efficiency, low cost, and physical and chemical stability. However, due to its wide bandgap (3.2 eV), TiO2 can only be excited by ultraviolet light, and cannot effectively utilize visible light, which accounts for 43% of the solar spectrum, or infrared light, which accounts for 52%. Furthermore, the typically small particle size of nano-TiO2 and its tendency to disperse in the liquid phase during the reaction complicate the separation, recovery, and reuse of the catalyst. To address these issues, magnetic materials have been introduced as carriers based on TiO2 to develop magnetic photocatalysts. These photocatalysts combine catalytic activity with magnetism. By applying an external magnetic field, the photocatalyst can be collected from the treated solution, avoiding secondary environmental pollution caused by the regenerated nanomaterial and enabling easy recycling. Among the numerous magnetic materials, Fe3O4 stands out due to its unique properties. As an important functional material, it has an inverse spinel structure and is a compound composed of ferrous oxide and ferric oxide. Some researchers used a solvent thermal method to prepare a Fe3O4@TiO2 core-shell structure. After the photocatalysis is completed, it can achieve 100% recovery within 30 seconds with only a simple magnetic attraction. The superparamagnetism of Fe3O4 effectively solves the problem of low recovery rate of TiO2 in practical applications. In addition, the Fe in Fe3O4 3+ It can be used as an absorber for photogenerated electron-hole pairs in the TiO2 lattice, thereby improving charge separation and enhancing photocatalytic activity.

[0006] Although the introduction of Fe3O4 significantly improves the recovery efficiency and photocatalytic activity of the catalyst, this method still fails to effectively solve the problem of low utilization of sunlight by TiO2 itself. Therefore, it is necessary to develop new strategies to enhance the spectral response range of titanium dioxide. Among them, combining with up-conversion technology is an effective means of photocatalytic response and utilization of near-infrared light. NaYF4:Yb,Tm based on lanthanide elements is a typical up-conversion luminescent material that matches the characteristic absorption peak of TiO2 well. Its anti-Stokes shift (Anti-Stokes) characteristics enable it to convert near-infrared light (NIR) into visible light or ultraviolet light, and has the advantages of long luminescence lifetime and stable optical properties. There are currently many reports on the use of up-conversion technology to modify TiO2 to improve photocatalytic activity, such as Yb 3+ / Tm 3+The co-doped NaGdF4@TiO2 core-shell structure increased the degradation efficiency of rhodamine B by 2.3 times. Therefore, by constructing a core-shell structure with the above-converted nanoparticles as the core and TiO2 as the shell, the efficiency of the catalyst in utilizing photons can be increased, the absorption edge of the material can be adjusted to visible light and near-infrared light, and the generation of ROS can be promoted.

[0007] In addition, researchers have found that in the photocatalytic process, continuous light assistance is crucial to maintaining the efficient progress of the catalytic reaction, but they have overlooked that in reality, light is often more complex and discontinuous. The intensity and periodic changes of light in real environments pose greater challenges to the efficiency and stability of the photocatalytic process. At the same time, traditional photocatalytic reactions often have huge energy loss problems, such as high-energy photon excitation, which not only increases the cost of water treatment, but also causes irrational use of energy. Therefore, how to improve the stability and efficiency of catalysts under discontinuous and dynamic light conditions and reduce unnecessary energy loss has become a major problem in the field of photocatalysis research. Against this background, researchers have gradually shifted their focus to the development of energy storage photocatalytic materials. Even when the light intensity changes or the reaction cycle is interrupted, this material can still maintain a certain catalytic activity, thereby maintaining continuous degradation of pollutants and reducing energy waste caused by changes in light. This ability is called memory catalysis (MC) or all-weather photocatalysis (RTCPs).

[0008] Precious metals (such as Ag and Au) are widely used in fields such as sensors due to their strong conductivity and electron storage capacity, and are strong candidates for realizing MC functions. For example, a study reported that Ag / TiO2 still degraded 12% of methylene blue dye within 3 hours after the light was turned off. However, Ag easily undergoes oxidation reactions with sulfides in the air, forming an oxide layer on the surface, resulting in a significant decrease in conductivity. In comparison, Au, as an inert metal, has higher chemical stability, corrosion resistance, and wear resistance. Gold nanoparticles (Au NPs) have been shown to have catalytic activity. At the same time, their unique properties can effectively broaden the spectral response range of titanium dioxide-based photocatalysts and improve the utilization of visible and near-infrared light. Studies have found that light propagating near AuNPs can cause the electrons and charge consistency to oscillate through the interaction between the oscillating electric field and free electrons, and resonate with the visible light frequency. This phenomenon is called surface plasmon resonance (SPR). The larger the diameter of Au NPs, the more the absorption band associated with surface plasmon resonance shifts toward near-infrared light, while the reflected light band gradually shifts toward visible light. The color of the prepared Au NPs solution will gradually change from red to purple. Trisodium citrate (Na3C6H5O7) is a surfactant and stabilizer that can absorb negatively charged citrate ions (C6H5O7 3-) adsorbed onto the surface of Au NPs to form a protective film to prevent the aggregation of nanoparticles that may occur during the synthesis process; in addition, Na3C6H5O7 3+ The formation of coordination effects controls the growth rate of Au NPs, thereby adjusting the size of gold nanoparticles. Therefore, by controlling the amount of Na3C6H5O7 added, large-diameter Au NPs are prepared and subsequently deposited on the surface of titanium dioxide-based photocatalysts, which can effectively collect visible and near-infrared light in the solar spectrum, thereby improving solar energy conversion efficiency.

[0009] The above studies have confirmed that Ag / TiO2 has a memory catalytic effect, Fe3O4@TiO2 can achieve magnetic recovery, and NaGdF4:Yb,Tm@TiO2 can expand the light response range. However, existing technologies have never been able to achieve the synergistic integration of the four. The ability of this complex system to treat organic dyes and antibiotics in water, and the synergistic relationship between memory catalytic ability and magnetic recovery performance have never been examined simultaneously. Summary of the Invention

[0010] To overcome the problems existing in the related art, the present invention discloses a plasma-enhanced magnetic nanocomposite photocatalyst with a memory catalytic effect, a preparation method, and an application thereof. Specifically, the invention relates to an Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite material with a memory catalytic effect. Driven by natural light, the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 exhibits efficient light energy conversion and pollutant degradation performance. When the light is turned off, the electrons stored in the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 are slowly released, continuing to drive the catalytic reaction, demonstrating a significant memory catalytic effect. After the experiment, the nanocomposite material is recovered under the action of an external magnetic field. Specifically, the present invention develops an Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst with a memory catalytic effect, efficient photocatalytic activity, magnetic separation properties, and environmental friendliness through a simple hydrothermal reaction, a sol-gel method, a calcination method, and an in-situ reduction deposition method. By combining the upconversion process, magnetic separation effect and plasma resonance characteristics, the recombination of electron-hole pairs is reduced, the efficiency of photogenerated carrier separation and redox ability are improved, thereby achieving the effect of efficiently treating organic pollutants in water and actual sewage under simulated and real sunlight driving.

[0011] The technical solution is as follows:

[0012] A plasma-enhanced magnetic nanocomposite photocatalyst with memory catalytic effect is a plasma-enhanced magnetic Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 core-shell structure nanocomposite material. The nanocomposite photocatalyst uses TiO2 as a matrix and is coated with NaYF4:Yb,Tm upconversion nanoparticles that can be excited by near-infrared light to obtain a NaYF4:Yb,Tm@TiO2 core-shell structure. Fe3O4 nanoparticles are compounded on this core-shell structure, and finally Au nanoparticle material is deposited on the surface of the shell layer.

[0013] Furthermore, the mass ratio of the Au nanoparticles in the NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite material is 3% to 5%, and the optimal mass ratio of the Au nanoparticles in the NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite material is 4%.

[0014] Furthermore, the nanocomposite photocatalyst has upconversion, surface plasmon resonance, memory catalysis and magnetic separation recovery characteristics.

[0015] Specifically, the core layer NaYF4:Yb,Tm upconversion nanoparticles of the nanocomposite photocatalyst can emit a characteristic ultraviolet spectrum under the excitation of 980nm near-infrared light, with its main peaks located at wavelengths of 290nm, 347nm and 362nm respectively; and the localized surface plasmon resonance phenomenon of Au nanoparticles can efficiently capture visible light of 520-550nm. The two together broaden the solar spectrum utilization range of the photocatalyst.

[0016] Specifically, the composite Fe3O4 on the nanocomposite photocatalyst NaYF4:Yb,Tm@TiO2 can give the material a portable magnetic separation and recovery characteristic, effectively solving the problem of nano photocatalyst recovery through an external magnetic field; and through Fe 2+ / Fe 3+ The mediating effect of the redox couple effectively promotes the transmission of photogenerated carriers between the TiO2-metal interface and inhibits electron-hole recombination. Its wide-spectrum light absorption characteristics (200-800nm) complement the ultraviolet light emitted by the upconversion material and the plasma resonance effect of Au nanoparticles, further broadening the light response range of the system.

[0017] Specifically, the nanocomposite photocatalyst Au deposition NaYF4:Yb,Tm@TiO2 / Fe3O4 has a unique memory catalytic ability. During the illumination stage, Au nanoparticles capture and store a large number of photogenerated electrons through the surface plasmon resonance effect. At the same time, Fe in Fe3O4 2+ / Fe 3+The redox pair further stabilizes the stored charge; when the light stops, these captured electrons are slowly released through the metal-semiconductor interface, continuing to drive the generation of reactive oxygen species, allowing the system to maintain the degradation of organic pollutants under light-free conditions.

[0018] The second object of the present invention is to provide a method for preparing a nanocomposite photocatalyst, comprising the following steps:

[0019] S1, NaYF4:Yb,Tm upconversion nanoparticles were synthesized by hydrothermal method;

[0020] S2, NaYF4:Yb,Tm@TiO2 core-shell structure prepared by sol-gel method;

[0021] S3, preparation of NaYF4:Yb,Tm@TiO2 / Fe3O4 nanopowder by calcination method;

[0022] S4, Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanopowders were prepared by in situ reduction deposition method.

[0023] Furthermore, step S1 includes the following steps:

[0024] Step S101: sodium hydroxide, oleic acid, and 12 ml of anhydrous ethanol were added to a 50 mL glass beaker and stirred thoroughly to obtain a white viscous liquid; 4.8 mmol of NH4F was added to the mixed solution and stirred continuously to obtain a clear solution; then, 1.5 ml of a 0.8 M LnCl3 solution (Y:Yb:Tm = 79.5:20:0.5) was added and stirred at room temperature for 20 minutes to form a translucent colloidal solution;

[0025] In step S102, the mixed solution obtained in step S101 is transferred to a Teflon-lined high-pressure reactor for hydrothermal reaction; after the solution is naturally cooled to room temperature, it is transferred to a sample tube and centrifuged at 4000 rpm for 10 minutes. The sample is washed three times with cyclohexane and ethanol respectively; finally, the powder is dried at 60°C to obtain NaYF4:Yb,Tm upconversion nanoparticle powder.

[0026] Further, step S2 includes the following steps: dissolving 1 mol of NaYF4:Yb,Tm in a certain amount of cyclohexane by ultrasonication, adding CTAB and 1 ml of The NaYF4:Yb,Tm solution was stirred vigorously in a flask. When the solution turned milky white, the system was placed in an 80°C water bath to evaporate cyclohexane. After the solution became clear, it was cooled at room temperature and centrifuged at 4000 min / r for 5 min to obtain CTAB-modified hydrophilic NaYF4:Yb,Tm; the above sample was washed twice with water and then redispersed in anhydrous ethanol; under magnetic stirring, the NaYF4:Yb,Tm / CTAB solution, 0.3 mL of 28 wt% ammonia water and 5 mL of water were fully mixed and stirred, and then 2 mol of isopropyl titanate in isopropanol solution was slowly added dropwise. The above solution was stirred and aged at room temperature for 12 h. After centrifugation at 4000 r / min, the sample was collected, washed twice with ethanol and isopropanol, and then dried at 60°C; finally, the nanopowder was calcined at 450°C in a muffle furnace for 3 h to obtain NaYF4:Yb,Tm@TiO2 nanomaterials.

[0027] Furthermore, step S3 includes the following steps: weighing 1g of NaYF4:Yb,Tm@TiO2, adding 10mg of Fe3O4 powder at a ratio of 1wt%, and grinding the two in an agate mortar for 10 minutes to ensure sufficient mixing; then placing the mixed powder in a muffle furnace, calcining it at a constant temperature of 350°C for 5h, and after natural cooling, obtaining NaYF4:Yb,Tm@TiO2 / Fe3O4 nanopowder.

[0028] Furthermore, step S4 includes the following steps: 0.1 g of NaYF4:Yb,Tm@TiO2 / Fe3O4 is uniformly dispersed in 100 mL of deionized water, 0.1 g / mL of HAuCl4·3H2O aqueous solution is added under continuous stirring, and the mixture is reacted at 80°C for 15 minutes; then 5 mL of freshly prepared 0.1 mmol / L trisodium citrate solution is quickly injected, and stirring is continued for 10 minutes; after the above solution is cooled at room temperature, the sample is collected after centrifugation at a speed of 4000 min / r, washed three times with deionized water, and then dried at 60°C to obtain Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanomaterial.

[0029] Furthermore, in step S101, the amount of sodium hydroxide added is 10-15 g, and the amount of oleic acid added is 10-20 ml.

[0030] Furthermore, in step S102, the hydrothermal reaction temperature is 150-200° C., and the hydrothermal time is 12-16 hours.

[0031] Furthermore, in step S2, the amount of CTAB added is 0.05-1.5 g, the calcination temperature is 350-600° C., and the calcination time is 3-6 h;

[0032] Furthermore, in step S3, the calcination temperature is programmed to increase at a heating rate of 20°C / min, and the calcination time is 4-5h;

[0033] Furthermore, the mass ratio of Au nanoparticles in the nanocomposite photocatalyst to the NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite material is 4%.

[0034] The third object of the present invention is to provide an application of the above-mentioned plasma-enhanced magnetic nanocomposite photocatalyst with memory catalytic effect in the treatment of degradative wastewater.

[0035] Furthermore, the wastewater is dye wastewater, antibiotic wastewater, actual urban sewage, etc.

[0036] Combining all the above technical solutions, the advantages and positive effects of the present invention are as follows:

[0037] (1) The Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 core-shell structure nanocomposite material produced by the present invention can be driven by natural light, utilizing natural light for efficient energy conversion, converting light energy into chemical energy. The degradation of pollutants in wastewater driven by natural light has the advantages of low carbon, environmental protection, and sustainable development. In addition, the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 core-shell structure nanocomposite material produced by the present invention has upconversion, magnetic separation, surface plasmon resonance, and memory catalysis properties. First, a simple hydrothermal method was used to synthesize NaYF4:Yb,Tm upconversion particles, which can emit characteristic ultraviolet spectra under the excitation of 980nm near-infrared light, and transfer it to TiO2 as an intermediate medium for energy transfer, thereby broadening the spectral response range of TiO2. The NaYF4:Yb,Tm@TiO2 core-shell structure synthesized by the sol-gel method can reduce the energy transfer distance between upconversion nanoparticles and TiO2, thereby improving the photon utilization rate. The NaYF4:Yb,Tm@TiO2 / Fe3O4 nanopowder prepared by the calcination method not only gives the material magnetic separation properties, but also Fe 2+ / Fe 3+The mediating effect of the redox couple effectively promotes the transmission of photogenerated carriers at the TiO2-metal interface and inhibits electron-hole recombination. The Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst prepared by in-situ reduction deposition method further captures 520-550nm visible light through the localized surface plasmon resonance phenomenon of Au nanoparticles, realizing the utilization range of the full solar spectrum of the composite photocatalytic system. In addition, under light excitation, Au nanoparticles can also capture and store a large number of photogenerated electrons, while Fe in Fe3O4 2+ / Fe 3 + The redox pair can further stably store charges. After the light stops, these captured electrons will be slowly released to drive the generation of reactive oxygen species, so that the system of the present invention can still maintain the continuous degradation of organic pollutants and actual wastewater under light-free conditions.

[0038] (2) Nano-TiO2 monomer photocatalyst has a narrow light response range, can only use ultraviolet light, and has low quantum efficiency. However, the present invention combines upconversion and surface plasmon resonance characteristics, which can effectively promote TiO2 response and use visible and near-infrared light, promote carrier separation efficiency, improve redox ability, and thus enhance photocatalytic activity. The present invention uses lanthanide-doped upconversion nanoparticles NaYF4:Yb, Tm, Yb 3+ ions have become widely used near-infrared photon collection centers due to their large absorption cross-section and efficient energy level matching characteristics. 3+ Ions have a unique energy level structure ( 3 H6→ 1 D2→ 3 F4→ 3 The H4 transition sequence enables efficient conversion of near-infrared light to shorter wavelengths (particularly the ultraviolet region (290-380nm) and deep blue (450-480nm), allowing it to be absorbed and utilized by the TiO2 shell. Simultaneously, the deposited Au nanoparticles exert surface plasmon resonance, effectively expanding the system's visible light response range, enabling full spectrum response to sunlight.

[0039] (3) Since NaYF4:Yb,Tm@TiO2 nanomaterials are highly dispersed in the aqueous system, the separation and recovery of photocatalysts becomes difficult. The composite Fe3O4 nanoparticles in the present invention solve the problem of material recovery while achieving a synergistic improvement in catalytic activity. The introduction of Fe3O4 gives the material excellent superparamagnetic properties, enabling it to be quickly separated by an external magnetic field, effectively overcoming the technical bottleneck of difficult nanocatalyst recovery. At the same time, the heterojunction structure formed between Fe3O4 and TiO2 generates a built-in electric field at the interface. This unique energy band matching not only promotes the efficient separation of photogenerated electron-hole pairs, but also promotes the recovery of photocatalysts through Fe3O4. 2+ / Fe 3+ The mediating effect of the redox couple accelerates the interfacial charge transfer and further improves the catalytic activity of TiO2-based nanocomposite photocatalysts.

[0040] (4) The nano-NaYF4:Yb,Tm@TiO2 / Fe3O4 composite system can only make full use of natural light, but under weak light or no light conditions, the catalytic performance will be greatly attenuated. The present invention deposits Au nanoparticles to give the material a unique memory catalytic function. Au nanoparticles not only significantly enhance the light capture ability in the visible light region through the surface plasmon resonance effect, but more importantly, as an electron storage center, they can effectively capture and store photogenerated electrons when illuminated to form a metallic Au-electron complex. When the light stops, these stored electrons will be slowly released through the Au-semiconductor interface, continuously driving the generation of active oxygen species, so that the catalytic system can still maintain a certain degradation activity under no light conditions. At the same time, the introduction of Au can also effectively promote the spatial separation of photogenerated carriers and inhibit the recombination of electron-hole pairs. The deposition of Au nanoparticles on NaYF4:Yb,Tm@TiO2 / Fe3O4 nanomaterials does not affect the other performance indicators of the material. On the contrary, through the synergistic effect with upconversion materials and magnetic components, it realizes the organic unity of the system's multifunctionality, such as light capture, charge separation, memory catalysis, and magnetic recovery, thereby further improving the ability of photocatalytic degradation of pollutants in water. Under the excitation of natural light, the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst exhibits efficient energy conversion and pollutant degradation performance. At the same time, the abundant active sites on the catalyst surface promote the continuous generation of reactive oxygen species. In actual water treatment applications, this nanophotocatalyst not only shows excellent degradation efficiency for organic pollutants (such as azo dyes, antibiotics, etc.), but also shows good adaptability in treating urban sewage with complex components.

[0041] (5) The expected benefits and commercial value after the transformation of the technical solution of the present invention are as follows: The present invention proposes a nanocomposite photocatalyst with memory catalytic ability that can be prepared on a large scale and a simple synthesis method thereof. The preparation process is environmentally friendly, green, low-cost, and has commercial application potential. Studies have shown that there is a clear market demand for photocatalytic treatment of wastewater. The Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite material with memory catalytic effect provided by the present invention can efficiently photocatalytically degrade malachite green dye, ciprofloxacin and nitrogen-containing organic pollutants in actual urban sewage in water, and convert them into harmless or low-toxic substances. Therefore, considering market demand, material manufacturing and practical applications, the plasma-enhanced magnetic nanocomposite photocatalyst with memory catalytic effect provided by the present invention is used for photocatalytic treatment of organic pollutants in water, and has high practical value and industrialization prospects in the field of environmental governance.

[0042] (6) The technical solution of the present invention has made systematic innovations to address the key defects of current photocatalytic water treatment technology, and has achieved a number of important breakthroughs in this field at home and abroad. Existing research mainly focuses on the performance optimization of nano-heterojunction photocatalysts under simulated light source conditions driven by electrical energy. This method essentially violates the core advantages of green and low-carbon photocatalytic technology. Nano-TiO2 monomer materials have the disadvantages of insufficient light utilization, low carrier separation efficiency and weak redox ability. In contrast, the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nano-composite photocatalyst developed by the present invention has a simple preparation process, realizes a truly natural light-driven high-efficiency catalytic system, and avoids the consumption of traditional energy and environmental pollution, embodying the concept of "green catalysis". NaYF4:Yb,Tm upconversion nanoparticles with near-infrared light response convert near-infrared light into ultraviolet light and then transmit it to TiO2, significantly broadening the light response range; Au nanoparticles not only enhance the visible light capture ability through the surface plasmon resonance effect, but also serve as electron storage centers to give the material memory catalytic function, realizing continuous catalysis under weak light or no light conditions. The introduction of Fe3O4 magnetic components overcomes the problem of separation and recovery of photocatalysts, and can further promote the effective separation of photogenerated carriers, improve redox ability, and produce more reactive oxygen species, thereby showing efficient degradation ability in the application of photocatalytic degradation of organic dyes, antibiotics in water and organic pollutants in actual urban sewage, providing an innovative material solution to solve the technical bottlenecks such as high energy consumption and low efficiency faced by the current water treatment field.

[0043] (7) The technical solution of the present invention solves the technical problems that people have been eager to solve but have never been able to solve successfully: The technical solution of the present invention provides theoretical guidance for the practical application of Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst with memory catalytic effect in the treatment of organic pollutants in water. The present invention provides a plasma-enhanced magnetic nanocomposite material with memory catalytic effect and its preparation method and application, which are used to treat organic pollutants in water and actual urban sewage, so as to solve the key bottleneck problems existing in the prior art, such as unsustainable nanomaterial driving energy, limited spectral response range, difficult recovery and separation, and insufficient redox ability, especially the engineering application problems such as low degradation efficiency of organic pollutants and poor actual wastewater treatment effect caused by this. The details are as follows: First, the preparation method of Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 composite photocatalyst provided by the present invention has the functions of full spectral response, plasma enhancement, magnetic separation and memory catalysis, thereby further improving the ability of photocatalytic degradation of pollutants in water. The preparation process is simple, green and controllable. Secondly, the nano-TiO2 monomer material has the disadvantages of insufficient light utilization, low carrier separation efficiency and weak redox ability. However, the NaYF4:Yb,Tm upconversion particles in the present invention can emit a characteristic ultraviolet spectrum under the excitation of 980nm near-infrared light, and transfer it to TiO2 as an intermediate medium for energy transfer. The addition of Fe3O4 not only makes the material paramagnetic, but also promotes the transmission of photogenerated carriers between the TiO2-metal interface. The deposited catalyst of Au nanoparticles can achieve a full spectral response range of the composite photocatalytic system through the localized surface plasmon resonance phenomenon; in addition, under light excitation, Au nanoparticles can also capture and store a large number of photogenerated electrons, and continue to drive the generation of reactive oxygen species after the light stops, exerting a memory catalytic effect. Finally, the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst undergoes a continuous and stable catalytic reaction driven by natural light, without producing harmful waste or emitting harmful gases, and achieves rapid separation and recovery. At the same time, the unique memory catalytic ability enables the composite photocatalytic system to adapt to changes in real weather conditions, and achieves good results in the photocatalytic degradation of malachite green dye, antibiotics and actual urban sewage in water.Under the conditions of natural light on a sunny day, 95.6% of the malachite green dye was degraded in just 20 minutes; under the weaker natural light on a cloudy day, the degradation rate of malachite green reached 94.9% after 40 minutes; the malachite green dye and ciprofloxacin products after photocatalytic degradation were low-toxic and harmless to cells; at the same time, in the photocatalytic reaction of actual sewage, the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst can degrade 94.3% of malachite green dye, 21.9% of ciprofloxacin and 85.7% of ammonia nitrogen, and when switched to a lightless environment, it can still maintain the degradation of pollutants, ultimately achieving a nitrogen conversion rate of 99.3%.

[0044] (8) The technical solution of the present invention overcomes technical prejudice: The current research on photocatalytic water treatment technology still has significant limitations, which are mainly reflected in the following aspects: the traditional method mainly relies on an analog light source system driven by electrical energy and uses a single-component TiO2 photocatalyst. This technical route has inherent defects such as high energy consumption, low light energy utilization, insufficient environmental friendliness, and difficulty in recycling, making it difficult to meet the requirements of green and sustainable development. In the present invention, the NaYF4:Yb,Tm upconversion nanoparticles convert light energy in the near-infrared region (980nm) into ultraviolet light, effectively expanding the spectral response range of TiO2; the introduction of Au nanoparticles not only enhances the light capture efficiency in the visible light region through the surface plasmon resonance effect, but also gives the material a continuous catalytic ability in weak light or no light environment due to its unique electron storage characteristics; the integration of Fe3O4 magnetic components solves the problem of separation and recovery of nanocatalysts, and the heterojunction structure formed by it and TiO2 also significantly promotes the separation efficiency of photogenerated carriers, greatly increasing the generation of active oxygen species. The material system exhibits efficient catalytic performance in the degradation of organic dyes, antibiotics in water, and organic pollutants in actual urban sewage. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present disclosure and, together with the description, serve to explain the principles of the present disclosure;

[0046] Figure 1 This is a graph showing the degradation efficiency of malachite green dye in water by Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst under simulated sunlight irradiation according to an embodiment of the present invention;

[0047] Figure 2 This is a graph showing the degradation efficiency of malachite green dye in water by Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst under 980nm near-infrared light irradiation according to an embodiment of the present invention;

[0048] Figure 3This is a graph showing the degradation efficiency of malachite green dye in water by Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst under visible light irradiation according to an embodiment of the present invention;

[0049] Figure 4 The degradation efficiency of malachite green dye in water by Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst under natural light on sunny and cloudy days according to the embodiment of the present invention is shown in the figure;

[0050] Figure 5 This is a graph showing the degradation efficiency of ciprofloxacin in water by Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst under simulated sunlight irradiation according to an embodiment of the present invention;

[0051] Figure 6 This is a graph showing the degradation efficiency of ciprofloxacin in water by Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst under 980nm near-infrared light irradiation according to an embodiment of the present invention;

[0052] Figure 7 This is a graph showing the degradation efficiency of ciprofloxacin in water by Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst under visible light irradiation according to an embodiment of the present invention;

[0053] Figure 8 This is a graph showing the photocatalytic efficiency of Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst prepared in an embodiment of the present invention for five cycles of degradation of malachite green dye in water;

[0054] Figure 9 This is a graph showing the photocatalytic efficiency of Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst prepared in an embodiment of the present invention for five cycles of degradation of ciprofloxacin in water;

[0055] Figure 10 This is a graph showing the degradation efficiency of malachite green dye in water by Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst under dark conditions after pre-illumination according to an embodiment of the present invention;

[0056] Figure 11 This is a graph showing the degradation efficiency of ciprofloxacin in water by Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst under dark conditions after pre-illumination according to an embodiment of the present invention;

[0057] Figure 12 This is a transmission scanning electron microscope image of the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst prepared in an embodiment of the present invention;

[0058] Figure 13 This is a graph showing the cell viability of human embryonic kidney 293 cells treated with degradation products of malachite green dye in water using Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalysts prepared in an embodiment of the present invention;

[0059] Figure 14 This is a flow chart of the preparation method of the nanocomposite photocatalyst of the present invention. DETAILED DESCRIPTION

[0060] To make the above-mentioned objects, features, and advantages of the present invention more readily apparent, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings. The following description sets forth numerous specific details to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art may make similar modifications without departing from the scope of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0061] The present invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0062] Example 1: A plasma-enhanced magnetic nanocomposite photocatalyst with a memory catalytic effect provided by an embodiment of the present invention is specifically a method for preparing an Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst with a memory catalytic effect, comprising the following steps:

[0063] (1) Sodium hydroxide, oleic acid and 12 ml of anhydrous ethanol were added to a 50 mL glass beaker and stirred thoroughly to obtain a white viscous liquid; 4.8 mmol of NH4F was added to the above mixed solution and stirred continuously to obtain a clear solution; then, 1.5 ml of 0.8 M LnCl3 solution (Y:Yb:Tm = 79.5:20:0.5) was added and stirred at room temperature for 20 min to form a translucent colloidal solution; then, the above mixed solution was transferred to a Teflon-lined high-pressure reactor for hydrothermal reaction; after the solution was naturally cooled to room temperature, it was transferred to a sample tube and centrifuged at 4000 rpm for 10 min. The sample was washed three times with cyclohexane and ethanol respectively; finally, the powder was dried at 60 °C to obtain NaYF4:Yb,Tm upconversion nanoparticle powder.

[0064] (2) 1 mol of NaYF4:Yb,Tm was ultrasonically dissolved in a certain amount of cyclohexane. CTAB and 1 ml of NaYF4:Yb,Tm solution were added to 20 ml of deionized water and stirred vigorously in a flask. When the solution turned milky white, the system was placed in an 80°C water bath to evaporate the cyclohexane. After the solution became clear, it was cooled at room temperature and centrifuged at 4000 min / r for 5 min to obtain CTAB-modified hydrophilic NaYF4:Yb,Tm. The sample was washed twice with water and then redispersed in anhydrous ethanol. Under magnetic stirring, the NaYF4:Yb,Tm / CTAB solution and 0.3 mL of 28wt% ammonia water and 5mL water were added, followed by the slow dropwise addition of 2mol isopropyl titanate isopropanol solution. The above solution was stirred and aged at room temperature for 12h. The sample was collected after centrifugation at 4000r / min, washed twice with ethanol and isopropanol, and then dried at 60°C. Finally, the nanopowder was calcined at 450°C in a muffle furnace for 3h to obtain NaYF4:Yb,Tm@TiO2 nanomaterials.

[0065] (3) Weigh 1 g of NaYF4:Yb,Tm@TiO2 and add 10 mg of Fe3O4 powder at a ratio of 1 wt%. Grind the two in an agate mortar for 10 min to ensure thorough mixing. Then, place the mixed powder in a muffle furnace and calcine at 350 °C for 5 h. After natural cooling, NaYF4:Yb,Tm@TiO2 / Fe3O4 nanopowder is obtained.

[0066] (4) 0.1 g of NaYF4:Yb,Tm@TiO2 / Fe3O4 was evenly dispersed in 100 mL of deionized water, and 0.1 g / mL of HAuCl4·3H2O aqueous solution was added under continuous stirring, and the mixture was reacted at 80°C for 15 min. Subsequently, 5 mL of freshly prepared 0.1 mmol / L trisodium citrate solution was quickly injected and the mixture was stirred for 10 min. After the solution was cooled to room temperature, the sample was collected by centrifugation at 4000 min / r, washed three times with deionized water, and then dried at 60°C to obtain Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanomaterials.

[0067] In an embodiment of the present invention, Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanomaterials exhibit highly efficient reactive oxygen species generation under full-spectrum excitation. Their unique feature is the perfect combination of photocatalysis and memory catalysis. During illumination, the nanomaterials synergistically produce highly reactive oxidizing species through multiple mechanisms, responsible for breaking chemical bonds in target pollutants. When switched to lightless conditions, electrons pre-stored in the Au nanoparticles are continuously released, allowing the degradation reaction to continue, ultimately achieving the complete degradation of organic pollutants from large molecules to small molecules, ultimately leading to complete mineralization into CO2 and H2O.

[0068] Through the above embodiments, the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst with memory catalytic effect provided by the present invention, when excited by near-infrared light, the NaYF4:Yb,Tm upconversion nanoparticles can respond and convert it into ultraviolet light and then pass it to TiO2; the introduction of precious metal Au significantly improves the material's absorption efficiency in the visible light region through the surface plasmon resonance effect, and its unique electron storage properties enable the photocatalyst to continue to play a catalytic role in low light or dark environments. The integration of the Fe3O4 component not only solves the technical problem of the difficulty in recycling nanophotocatalysts, but also effectively promotes the separation of photogenerated electron-hole pairs, greatly enhances the redox performance of the composite photocatalytic system, and promotes the generation of more highly active oxygen species. This innovative design enables the nanocomposite photocatalytic material to exhibit efficient degradation performance when treating simulated wastewater containing organic dyes and antibiotics and actual urban sewage. The present invention combines NaYF4:Yb,Tm, TiO2, Fe3O4 and Au to prepare an Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst with full spectrum response, superparamagnetism, high-efficiency photocatalytic activity, memory catalytic properties and good reusability. The nanocomposite photocatalyst exhibits excellent photocatalytic effect in the application of treating organic pollutants in water and actual wastewater.

[0069] Example 2, an experiment of photocatalytic degradation of malachite green and ciprofloxacin in water using multiple composite nanocomposite photocatalysts prepared in Example 1 of the present invention under simulated sunlight, 980nm infrared light, visible light and natural light, comprising the following steps:

[0070] a. Prepare 50 mL (10 mg / L) of malachite green dye or ciprofloxacin solution in a 50 mL quartz beaker and disperse 10 mg of nanomaterial in the prepared solution.

[0071] b. Place the quartz beaker obtained in step a in a container filled with cooling water and stir in the dark for 40 minutes to reach adsorption-desorption equilibrium.

[0072] c. Expose the suspension to different light sources for photocatalytic experiments. Remove 3 mL of the dye or antibiotic-nanomaterial mixed solution at -40, -20, 0, 20, 40, 60, 80, 100, and 120 min, centrifuge, and collect 2.5 mL of the supernatant.

[0073] d. Use a UV-visible spectrophotometer to measure the absorbance of the supernatant at its maximum absorption wavelength. The maximum absorption wavelengths of malachite green, methylene blue, methylene orange, and rhodamine B dyes are 618, 664, 463, and 554 nm, respectively; the maximum absorption wavelength of ciprofloxacin is 268 nm.

[0074] e. The concentration of dye or antibiotic is calculated based on the standard curve, and the photocatalytic degradation efficiency is calculated using the following formula.

[0075] Degradation rate = (1-C / C0) x 100% (1)

[0076] Where: C0 is the concentration of the solution when it reaches adsorption-desorption equilibrium; C is the concentration of the solution after illumination.

[0077] f. Perform photocatalytic experiments under 980nm infrared light and visible light irradiation, and the specific steps are the same as steps ae above.

[0078] g. Conduct photocatalytic experiments under natural conditions of bright sunlight on a sunny day and dim light on a cloudy day. The specific steps are the same as those in steps a. In step c, the prepared solution is placed in a light-proof reaction vessel (e.g., a beaker wrapped in tinfoil), and then transferred outdoors to a natural light environment for subsequent photocatalytic experiments.

[0079] Figure 1Figure 2 shows the degradation efficiency of malachite green in water using unphotocatalyzed malachite green, NaYF4:Yb,Tm, NaYF4:Yb,Tm@TiO2, NaYF4:Yb,Tm@TiO2 / Fe3O4, Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4, Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 in the dark, and commercial TiO2 and Fe3O4 under simulated sunlight. After 2 hours of simulated sunlight exposure, the unphotocatalyzed malachite green dye was highly stable, indicating no self-degradation. The degradation rates of the NaYF4:Yb,Tm group and the blank group were similar, indicating that NaYF4:Yb,Tm has no photocatalytic activity. After the photocatalytic system reached adsorption equilibrium after 40 minutes, Fe3O4 degraded 43.5% of malachite green dye under the drive of simulated sunlight, indicating that it has a certain photocatalytic effect. After the materials are composited, NaYF4:Yb,Tm@TiO2, NaYF4:Yb,Tm@TiO2 / Fe3O4 and Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 all show good photocatalytic degradation ability. The photocatalytic degradation efficiency of NaYF4:Yb,Tm@TiO2 for malachite green dye is 81.3%, and that of NaYF4:Yb,Tm@TiO2 / Fe3O4 is 71.6%. The photocatalytic degradation activity of Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 is the highest, with a removal rate of 94.1% of malachite green dye within 2 hours.

[0080] Figure 2 and Figure 3This is a graph showing the degradation efficiency of malachite green dye in water by NaYF4:Yb,Tm@TiO2, NaYF4:Yb,Tm@TiO2 / Fe3O4 and Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalysts containing different Au deposition mass ratios under 980nm near-infrared light and visible light irradiation. Under the irradiation of 980nm near-infrared light source, after 8h, the degradation efficiencies of NaYF4:Yb,Tm@TiO2, NaYF4:Yb,Tm@TiO2 / Fe3O4, NaYF4:Yb,Tm@TiO2 / Fe3O4-3Au, NaYF4:Yb,Tm@TiO2 / Fe3O4-4Au and NaYF4:Yb,Tm@TiO2 / Fe3O4-5Au were 41.5%, 48.7%, 59.1%, 65.0% and 62.3%, respectively. Under visible light irradiation of wavelength ≥420 nm, the degradation efficiencies of NaYF4:Yb,Tm@TiO2, NaYF4:Yb,Tm@TiO2 / Fe3O4, NaYF4:Yb,Tm@TiO2 / Fe3O4-3Au, NaYF4:Yb,Tm@TiO2 / Fe3O4-4Au, and NaYF4:Yb,Tm@TiO2 / Fe3O4-5Au were 34.9%, 41.3%, 45.2%, 48.5%, and 41.9%, respectively, after 2 h. These results demonstrate that the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalysts exhibit excellent photoresponsiveness to visible and near-infrared light and can effectively photocatalytically degrade organic pollutants in water.

[0081] Figure 4 Figure 2 shows the degradation efficiency of malachite green dye in water using an Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst under both strong sunlight on a sunny day and weak sunlight on a cloudy day, according to an embodiment of the present invention. As can be seen, under strong sunlight on a sunny day, the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 photocatalyst almost completely degraded 10 mg / L of malachite green dye by 95.6% in just 20 minutes, a degradation efficiency six times higher than under simulated sunlight. Even under weaker sunlight on a cloudy day, 94.9% of the malachite green dye was degraded after 40 minutes. This demonstrates that the material can effectively utilize sunlight for degradation under diverse conditions. These results demonstrate that the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst can adapt to changing environmental conditions and exhibits broad application prospects in efficiently utilizing natural sunlight to treat organic pollutants in water.

[0082] Figure 5Figure 2 shows the degradation efficiency of ciprofloxacin in water using untreated ciprofloxacin, NaYF4:Yb,Tm, NaYF4:Yb,Tm@TiO2, NaYF4:Yb,Tm@TiO2 / Fe3O4, Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 with different Au mass ratios, and Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 as a dark control under simulated sunlight. After 2 hours of xenon lamp irradiation, ciprofloxacin without photocatalyst was highly stable, indicating no self-degradation. The degradation rates of the NaYF4:Yb,Tm group and the blank group were similar, indicating that NaYF4:Yb,Tm has no photocatalytic activity. After the photocatalytic system reached adsorption equilibrium after 40 minutes, driven by simulated sunlight, NaYF4:Yb,Tm@TiO2, NaYF4:Yb,Tm@TiO2 / Fe3O4, NaYF4:Yb,Tm@TiO2 / Fe3O4-3Au, NaYF4:Yb,Tm@TiO2 / Fe3O4-4Au and NaYF4:Yb,Tm@TiO2 / Fe3O4-5Au all had certain photocatalytic degradation abilities for ciprofloxacin. The photocatalytic degradation efficiency of NaYF4:Yb,Tm@TiO2 for ciprofloxacin was 66.7%, and that of NaYF4:Yb,Tm@TiO2 / Fe3O4 was 77.4%. After the introduction of Au nanoparticles, the degradation performance of Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanophotocatalysts with all different Au mass ratios was better than that of NaYF4:Yb,Tm@TiO2 and NaYF4:Yb,Tm@TiO2 / Fe3O4. Among them, NaYF4:Yb,Tm@TiO2 / Fe3O4-4Au had the highest photocatalytic degradation activity, with a removal rate of 88.9% for ciprofloxacin within 2 hours. After Au deposition, the photocatalyst showed excellent photocatalytic degradation performance on both organic dyes and antibiotics. On the one hand, it was attributed to the fact that after Fe3O4 was composited with TiO2, Fe 3+ It can not only enter the electron capture position, but also the hole capture position, thereby forming a shallow charge trap to reduce the electron-hole recombination; on the other hand, the deposition of Au nanoparticles can move the Fermi level in a more negative direction, thereby improving the interface charge transfer efficiency.

[0083] Figure 6 and Figure 7This is a graph showing the degradation efficiency of ciprofloxacin in water by NaYF4:Yb,Tm@TiO2, NaYF4:Yb,Tm@TiO2 / Fe3O4 and Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalysts containing different Au deposition mass ratios under 980nm near-infrared light and visible light irradiation. Under 980nm near-infrared light irradiation, the degradation efficiencies of NaYF4:Yb,Tm@TiO2, NaYF4:Yb,Tm@TiO2 / Fe3O4, NaYF4:Yb,Tm@TiO2 / Fe3O4-3Au, NaYF4:Yb,Tm@TiO2 / Fe3O4-4Au, and NaYF4:Yb,Tm@TiO2 / Fe3O4-5Au were 9.1%, 14.7%, 15.6%, 20.3%, and 12.0%, respectively, after 8 hours. Under visible light irradiation of wavelength ≥420 nm, the degradation efficiencies of NaYF4:Yb,Tm@TiO2, NaYF4:Yb,Tm@TiO2 / Fe3O4, NaYF4:Yb,Tm@TiO2 / Fe3O4-3Au, NaYF4:Yb,Tm@TiO2 / Fe3O4-4Au, and NaYF4:Yb,Tm@TiO2 / Fe3O4-5Au were 27.7%, 33.7%, 30.1%, 46.8%, and 31.1%, respectively, after 2 h. These results demonstrate that the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalysts are responsive to both visible and near-infrared light and can effectively photocatalytically degrade antibiotics in water.

[0084] Figure 8 This graph shows the photocatalytic efficiency of the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst, prepared in this embodiment of the present invention, for the degradation of malachite green dye in water over five cycles. The results show that the degradation rate of malachite green dye by the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 gradually decreased from 94.1% to 91.5%, 90.1%, 85.1%, and 82.0%. Even after five cycles, the composite photocatalytic system maintained a degradation efficiency above 80%.

[0085] Figure 9This graph shows the photocatalytic efficiency of the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst, prepared in an embodiment of the present invention, over five cycles of degradation of ciprofloxacin in water. The results show that the degradation rate of ciprofloxacin by the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 gradually decreased from 88.9% to 82.2%, 79.4%, 75.8%, and 72.3%. The degradation efficiency of the composite photocatalytic system remained above 70% after five cycles. These results demonstrate that the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst exhibits relatively stable reusability and stability, whether targeting organic dyes or emerging antibiotic contaminants in water.

[0086] Example 3. A plasma-enhanced magnetic nanocomposite photocatalyst with a memory catalytic effect prepared using Example 1 provided in an embodiment of the present invention specifically relates to an Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite material with a memory catalytic effect. The nanocomposite photocatalyst is based on TiO2 and is coated with NaYF4:Yb,Tm upconversion nanoparticles that can be excited by near-infrared light. Fe3O4 nanoparticles are compounded on the basis of this core-shell structure, and finally Au nanoparticle material is deposited on the surface of the shell layer.

[0087] The Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst with memory catalytic effect is represented by "NaYF4:Yb,Tm@TiO2 / Fe3O4-Au". The mass ratio of Au nanoparticles in the NaYF4:Yb,Tm@TiO2 / Fe3O4-Au nanocomposite material is 3% to 5%, with the optimal mass ratio being 4%.

[0088] For example: In the embodiment of the present invention, when the mass ratio of Au nanoparticles in the NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite material in the nanocomposite photocatalyst is 4%, it is expressed as "NaYF4:Yb,Tm@TiO2 / Fe3O4-4Au".

[0089] Example 4. A plasma-enhanced magnetic nanocomposite photocatalyst with a memory catalytic effect provided by an embodiment of the present invention has a core layer of NaYF4:Yb,Tm upconversion nanoparticles that can emit a characteristic ultraviolet spectrum under the excitation of 980nm near-infrared light, with its main peaks located at wavelengths of 290nm, 347nm and 362nm respectively; and the localized surface plasmon resonance phenomenon of Au nanoparticles can efficiently capture visible light of 520-550nm. The two together broaden the solar spectrum utilization range of the photocatalyst.

[0090] Example 5. A plasma-enhanced magnetic nanocomposite photocatalyst with a memory catalytic effect is provided in an embodiment of the present invention. The composite Fe3O4 on NaYF4:Yb,Tm@TiO2 can give the material superparamagnetic properties, which can effectively solve the problem of nanophotocatalyst recovery through an external magnetic field.

[0091] Example 6: A plasma-enhanced magnetic nanocomposite photocatalyst with a memory catalytic effect, provided by an embodiment of the present invention, possesses unique memory catalytic capabilities. Through a two-stage "illumination-dark state" reaction process, in the pre-illumination stage, the nanocomposite photocatalyst, under the excitation of simulated sunlight, selectively captures and stores photogenerated electrons in Au nanoparticles. After transitioning to the dark state, analysis using a UV-visible spectrophotometer reveals a continuous downward trend in the concentration of the target pollutant after the illumination ends, confirming that the slow release of stored electrons drives the dark state catalytic reaction.

[0092] Example 7: A plasma-enhanced magnetic nanocomposite photocatalyst with a memory catalytic effect, provided by an embodiment of the present invention, effectively degrades malachite green dye and ciprofloxacin solution within a certain period of time under simulated sunlight. Under natural sunlight on a sunny day, 95.6% of the malachite green dye was degraded in just 20 minutes. Under weaker natural sunlight on a cloudy day, the degradation rate reached 94.9% after 40 minutes. The resulting malachite green and ciprofloxacin products exhibited low toxicity to cells and demonstrated excellent biosafety.

[0093] Example 8. Application of the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite with memory catalytic effect provided by the present invention in the degradation of organic pollutants in water, treatment of actual urban sewage, and memory catalytic effect. Specifically: Under natural light, the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite with memory catalytic effect can effectively treat organic pollutants in actual urban sewage, degrading 94.3% of malachite green dye, 21.9% of ciprofloxacin, and 85.7% of ammonia nitrogen in actual urban sewage. Moreover, when placed in a lightless environment, the degradation of pollutants can still be maintained, ultimately achieving a nitrogen conversion rate of 99.3%.

[0094] In the above application, the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst with memory catalytic effect provided by the present invention, when excited by near-infrared light, the NaYF4:Yb,Tm upconversion nanoparticles can respond and convert it into ultraviolet light and then pass it to TiO2; the introduction of precious metal Au significantly improves the material's absorption efficiency in the visible light region through the surface plasmon resonance effect, and its unique electron storage characteristics enable the photocatalyst to continue to play a catalytic role in low light or dark environments. The integration of the Fe3O4 component not only solves the technical problem of the difficulty in recycling nanophotocatalysts, but also effectively promotes the separation of photogenerated electron-hole pairs, greatly enhances the redox performance of the composite photocatalytic system, and promotes the generation of more highly active oxygen species. This innovative design enables the nanocomposite photocatalytic material to exhibit efficient degradation performance when treating simulated wastewater containing organic dyes and antibiotics and actual urban sewage. The present invention combines NaYF4:Yb,Tm, TiO2, Fe3O4 and Au to prepare an Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst with full spectrum response, superparamagnetism, high-efficiency photocatalytic activity, memory catalytic properties and good reusability. The nanocomposite photocatalyst exhibits excellent photocatalytic effect in the application of treating organic pollutants in water and actual wastewater.

[0095] Example 9: This embodiment of the present invention provides a method for preparing an Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite material having a memory catalytic effect, comprising the following steps:

[0096] a. Add sodium hydroxide, oleic acid and 12ml of anhydrous ethanol to a 50ml glass beaker and stir thoroughly to obtain a white viscous liquid.

[0097] b. 4.8 mmol of NH4F was added to the mixed solution obtained in step a, and the mixture was stirred continuously to obtain a clear solution; subsequently, 1.5 ml of 0.8 M LnCl3 solution (Y: Yb: Tm = 79.5: 20: 0.5) was added and stirred at room temperature for 20 min to form a translucent colloidal solution;

[0098] c. The mixed solution obtained in step b was transferred to a Teflon-lined high-pressure reactor for a hydrothermal reaction; after the solution was naturally cooled to room temperature, it was transferred to a sample tube and centrifuged at 4000 rpm for 10 minutes. The sample was washed three times with cyclohexane and ethanol respectively; finally, the powder was dried at 60°C to obtain NaYF4:Yb,Tm upconversion nanoparticle powder.

[0099] d. Dissolve 1 mol of NaYF4:Yb,Tm in a certain amount of cyclohexane by ultrasonication. Add CTAB and 1 ml of NaYF4:Yb,Tm solution to 20 ml of deionized water and stir vigorously in a flask. When the solution turns milky white, place the system in an 80°C water bath to evaporate the cyclohexane.

[0100] e. After the solution obtained in step d becomes clear, it is cooled at room temperature and centrifuged at 4000 min / r for 5 min to obtain CTAB-modified hydrophilic NaYF4:Yb,Tm; the sample is washed twice with water and then redispersed in anhydrous ethanol;

[0101] f. The solution obtained in step e was thoroughly mixed and stirred under magnetic stirring: NaYF4: Yb, Tm / CTAB solution, 0.3mL28wt% ammonia and 5mL water, followed by slow dropwise addition of 2mol of isopropyl titanate in isopropanol,

[0102] g. The solution obtained in step f was stirred and aged at room temperature for 12 h, and the sample was collected after centrifugation at 4000 r / min, washed twice with ethanol and isopropanol, and then dried at 60 ℃;

[0103] h. The nanopowder obtained in step g was calcined in a muffle furnace at 450°C for 3h to obtain NaYF4:Yb,Tm@TiO2 nanomaterials.

[0104] i. Weigh 1g of NaYF4: Yb, Tm@TiO2 and add 10mg of Fe3O4 powder at a ratio of 1wt%. Grind the two in an agate mortar for 10min to ensure thorough mixing.

[0105] j. The mixed powder obtained in step i was placed in a muffle furnace and calcined at a constant temperature of 350°C for 5h. After natural cooling, NaYF4:Yb,Tm@TiO2 / Fe3O4 nanopowder was obtained.

[0106] k. Disperse 0.1 g of NaYF4:Yb,Tm@TiO2 / Fe3O4 evenly in 100 mL of deionized water. Add 0.1 g / mL of HAuCl4·3H2O aqueous solution under continuous stirring and react at 80°C for 15 min.

[0107] l In step k, the solution obtained was quickly injected into a freshly prepared 5mL 0.1mmol / L trisodium citrate solution and stirred for 10min;

[0108] m. After the solution prepared in step 1 was cooled at room temperature, the sample was collected by centrifugation at a speed of 4000 min / r, washed three times with deionized water, and then dried at 60°C to obtain Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanomaterials.

[0109] Preferably, the NaYF4:Yb,Tm nanoparticles prepared in step c have an irregular hexagonal morphology and a size of about 10 to 30 nm.

[0110] Preferably, in step h, nano-TiO2 forms a uniform shell coating on the surface of NaYF4:Yb,Tm nanoparticles, constructing a typical core-shell structure with a shell thickness of about 5 nm, and causing agglomeration between particles.

[0111] Preferably, the compounding of the Fe3O4 nanoparticles in step j significantly increases the interaction between the NaYF4:Yb,Tm@TiO2 / Fe3O4 nanomaterial particles, forming a typical spherical agglomerate structure.

[0112] Preferably, in step m, the Au nanoparticles are relatively evenly distributed on the surface of the nano-TiO2 shell layer, and the particle size is about 5 to 10 nm.

[0113] The transmission scanning electron microscope photo of the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite prepared in Example 9 of the present invention is shown in FIG. Figure 12 The results show that after high-temperature calcination, the surface of the NaYF4:Yb,Tm nanoparticles was successfully coated with a TiO2 nanoshell. The incorporation of Fe3O4 resulted in the core-shell nanomaterial forming a typical spherical aggregate structure. Furthermore, the relatively uniform deposition of Au nanoparticles on the NaYF4:Yb,Tm@TiO2 / Fe3O4 substrate was clearly observed. This structural feature confirms the successful synthesis of the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 core-shell nanocomposite.

[0114] Example 10, in order to further explore the memory catalytic effect of the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst prepared in Example 9 of the present invention, comprises the following steps:

[0115] a. Add 10mg Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite to 50mL pure water and place it in a container filled with cooling water for light pretreatment under simulated sunlight.

[0116] b. After the pre-illumination period, malachite green dye or ciprofloxacin was added to the suspension. The lights were turned off to simulate dark conditions, and the pollutant catalytic degradation experiment was conducted for 160 minutes. Every 20 minutes, 3 mL of the dye or antibiotic-nanomaterial mixture was aspirated and centrifuged, and 2.5 mL of the supernatant was collected.

[0117] c. Use a UV-visible spectrophotometer to measure the absorbance of the supernatant at its maximum absorption wavelength. The maximum absorption wavelength of malachite green is 618 nm; the maximum absorption wavelength of ciprofloxacin is 268 nm.

[0118] d. The concentration of dye or antibiotic was calculated based on the standard curve, and the photocatalytic degradation efficiency was calculated using formula (1).

[0119] Figure 10 This is a graph showing the degradation efficiency of malachite green dye in water by Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst in the dark after 1, 2, 3, 4 and 5 hours of pre-illumination according to an embodiment of the present invention. The dark control results show that after the system reaches adsorption-desorption equilibrium, the degradation rate of malachite green dye remains almost unchanged, indicating that the dye molecules are stable and will not self-degrade under no-light conditions. It also shows that the activation of the photocatalyst and the performance of its degradation performance must rely on the driving force of light conditions. Compared with pre-illumination at other times, 4 hours of pre-illumination has the best degradation effect on malachite green dye. Within 160 minutes, the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst degraded 43.7% of the malachite green dye. This shows that the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst has a "memory catalysis" effect.

[0120] Figure 11 Figure 2 shows the degradation efficiency of ciprofloxacin in water using the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst in the dark after 1, 2, 3, 4, and 5 hours of pre-illumination. The dark control results show that the ciprofloxacin degradation rate remains almost unchanged after the system reaches adsorption-desorption equilibrium, demonstrating the stability of the antibiotic molecule in the absence of light and its resistance to self-degradation. This also suggests that the activation of the photocatalyst and its degradation performance are driven by light. Ciprofloxacin degradation initially increases and then decreases with increasing pre-illumination time. A 2-hour pre-illumination period achieves the best degradation of ciprofloxacin, reaching a degradation rate of 22.4% at 160 minutes. This demonstrates that the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst exhibits a "memory catalysis" effect. However, this effect has a maximum limit, likely due to the fact that longer illumination increases the recombination rate of photogenerated electron-hole pairs, thereby reducing the catalytic effect.

[0121] Example 11. In order to evaluate the biological toxicity of the product after the degradation of malachite green dye by the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst prepared in Example 9, the cytotoxicity test of malachite green supernatant samples with different degradation times was carried out using the thiazolyl blue assay method.

[0122] a. Human embryonic kidney 293 cells in logarithmic growth phase were cultured at 1×10 4 The cells were seeded in 96-well plates and cultured in a 37°C incubator with 5% CO2 for 24 h.

[0123] b. Remove the culture medium from the culture plate, add 100 μL of malachite green dye degradation products with different photocatalytic degradation times (-40, -20, 0, 20, 40, 60, 80, 100, 120 min) under simulated sunlight to the culture medium, mix them with 100 μL of serum-free culture medium and add them to the culture plate, and use 100 μL of pure water and 100 μL of serum-free culture medium as the control group, and continue to culture in a 37°C incubator with 5% CO2 for 24 h.

[0124] c. After culturing for 24 h, add 20 μL of 0.5 mg / mL MTT solution to each well in the dark and continue culturing for 4 h.

[0125] d. Aspirate the liquid from the wells and add 150 μL of dimethyl sulfoxide solution to each well. After shaking on a shaker for 10 minutes, measure the absorbance at 490 nm using a microplate reader and calculate the cell viability based on the average value of 6 parallel wells. Each experiment was repeated three times. The formula for calculating the cell growth inhibition rate is as follows:

[0126] Cell viability (%) = (1-OD t / OD0)×100% (2)

[0127] Among them: OD0 is the OD value of the control group, OD t is the OD value of the product after treatment.

[0128] Figure 13This is a graph showing the cell viability of human embryonic kidney 293 cells treated with the degradation products of malachite green in water using the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst according to an embodiment of the present invention. As shown, the cell viability of cells co-cultured with the initial malachite green dye was only 0.0%, indicating the low biosafety of malachite green dye. As the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst progressed, the toxicity of the degradation products gradually decreased, while cell viability increased. The cell viability from -40 to 40 min was statistically significant compared to the control group (****p<0.0001). Among the degradation products after 120 minutes of photocatalysis, the cell viability was 89.0%. This result indicates that after 2 hours of photocatalytic reaction, the malachite green dye was degraded and mineralized into a low-toxic complex, demonstrating the excellent biosafety and environmental friendliness of the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst.

[0129] Example 12, in order to systematically evaluate the environmental application performance of the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst prepared in Example 9, the photocatalytic degradation of actual urban sewage was selected, and the memory catalytic performance of the nanocomposite material under actual conditions was examined. The specific experimental steps are as follows:

[0130] a. Actual municipal sewage was collected from an urban river (117°18'E - 39°11'N) and filtered for photocatalytic experiments. 150 mL of municipal sewage was placed in a 200 mL quartz beaker, and a 10 mg / mL malachite green dye and 5 mg / mL ciprofloxacin solution were added to create a mixture of nitrogen-containing dye and antibiotics.

[0131] b. Add 30 mg of the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst to the 150 ml mixture and stir in the dark for 40 minutes to achieve adsorption-desorption equilibrium. Then, perform a photocatalytic experiment under simulated sunlight for 6 hours. The photocatalytic solution was centrifuged and the supernatant was collected. Then, turn off the lights and perform a 12-hour dark catalytic experiment to simulate a realistic dark environment, verifying the nanocomposite's memory catalytic performance under dark conditions. Similarly, the dark catalytic solution was centrifuged to obtain the supernatant.

[0132] c. The pH values ​​of the two supernatants obtained in step b were obtained by a laboratory pH meter (FE20). The absorbance of malachite green dye at the maximum absorption wavelength was measured using a UV-visible spectrophotometer, and the degradation rate was calculated by formula (1). The degradation rate of ciprofloxacin was calculated as above. The concentrations of three nitrogen indicators (ammonia nitrogen, nitrite nitrogen, and nitrate nitrogen) in the supernatant were measured by a portable three-nitrogen detector (GDYS-302S). According to previous studies, the products of photocatalytic degradation of ammonia nitrogen mainly include nitrite nitrogen, nitrate nitrogen, and nitrogen gas. Therefore, the degradation rate and product conversion rate can be calculated by formula (3-6):

[0133]

[0134] Nitrogen conversion rate (%) = 1 - nitrite nitrogen conversion rate - nitrate nitrogen conversion rate (6)

[0135] Where: C0 and C are the concentrations of the target substance in the solution before and after the photocatalytic reaction, respectively.

[0136] As shown in Table 1 below, this is a table of physical and chemical parameters of the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst in the treatment of actual urban sewage under simulated sunlight irradiation and dark background at night.

[0137] Table 1

[0138]

[0139] After 6 hours of photocatalytic treatment, the wastewater pH increased, likely due to the formation of intermediates during the photocatalytic degradation process. Malachite green dye was almost completely degraded, and the concentration of ciprofloxacin decreased, with degradation rates of 94.3% and 25.2%, respectively. The experimental results demonstrate that the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst exhibits excellent degradation efficiency for organic pollutants in municipal wastewater, demonstrating its practical application in advanced oxidation water treatment processes. Furthermore, the nanocomposite photocatalyst demonstrated excellent removal efficiency for ammonia nitrogen in municipal wastewater. Ammonia nitrogen is a major pollutant in water bodies, and its excessive discharge poses a serious threat to the ecological environment and human health. In this study, ammonia nitrogen levels were significantly reduced, reaching a degradation rate of 85.7% after 6 hours of photocatalytic treatment. The small amounts of nitrite and nitrate nitrogen produced during the removal process were low (<1 mg / L), with conversion rates below 5%, making them negligible. According to the ammonia nitrogen product balance, the remaining ammonia nitrogen is mainly converted into harmless nitrogen. The calculation shows that the nitrogen conversion rate is 97.8%, indicating that the nanocomposite material has good environmental friendliness and is in line with the concept of "green catalysis".

[0140] After 6 hours of simulated sunlight exposure, this study also conducted a 12-hour dark catalytic experiment with the lights off to better simulate real-world weather conditions. This experiment further demonstrated the memory catalytic properties of the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite. The experimental results showed that after 12 hours of simulated darkness, the levels of malachite green dye, ciprofloxacin, and ammonia nitrogen all changed to some extent, and the nitrogen conversion rate further increased, ultimately reaching 99.3%, indicating that nearly all ammonia nitrogen was converted to environmentally friendly nitrogen. Therefore, even in darkness, the Au nanoparticles were able to release the electrons stored during illumination, allowing the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst to exert its memory catalytic properties and continue to treat mixed pollutants. The above results show that the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst has a satisfactory treatment effect on urban mixed sewage under actual environmental background, which fully proves that the Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite photocatalyst has good prospects in the field of water pollution control and can provide a practical technical solution for solving water environment problems in the current natural environment.

[0141] In the above embodiments, the description of each embodiment has its own focus. For parts that are not described or recorded in detail in a certain embodiment, reference can be made to the relevant description of other embodiments.

[0142] The above description is only a preferred specific implementation method of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with this technical field within the technical scope disclosed by the present invention and within the spirit and principles of the present invention should be covered by the scope of protection of the present invention.

[0143] The above description is only a preferred embodiment of the present invention. It should be understood that the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative work are within the scope of protection of the present invention. The present invention is not limited to the form disclosed herein and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments. Changes and modifications made by those skilled in the art do not depart from the spirit and scope of the present invention and should be within the scope of protection of the claims appended to the present invention.

Claims

1. A plasma-enhanced magnetic nanocomposite photocatalyst with memory catalytic effect, characterized by: The nanocomposite photocatalyst is an Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite material. The nanocomposite photocatalyst uses TiO2 as a matrix and is coated with NaYF4:Yb,Tm upconversion nanoparticles that can be excited by near-infrared light to obtain a NaYF4:Yb,Tm@TiO2 core-shell structure. Fe3O4 nanoparticles are compounded on the basis of the core-shell structure, and finally Au nanoparticle material is deposited on the surface of the shell layer.

2. The plasma-enhanced magnetic nanocomposite photocatalyst with memory catalytic effect according to claim 1, characterized in that: The mass ratio of the Au nanoparticles in the NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite material is 3% to 5%, and the optimal mass ratio of the Au nanoparticles in the NaYF4:Yb,Tm@TiO2 / Fe3O4 nanocomposite material is 4%.

3. The plasma-enhanced magnetic nanocomposite photocatalyst with memory catalytic effect according to claim 1, characterized in that: The nanocomposite photocatalyst has upconversion, surface plasmon resonance, memory catalysis and magnetic separation recovery characteristics. The core layer NaYF4:Yb,Tm upconversion nanoparticles of the nanocomposite photocatalyst can emit a characteristic ultraviolet spectrum under the excitation of 980nm near-infrared light, and its main peaks are located at wavelengths of 290nm, 347nm and 362nm respectively; the localized surface plasmon resonance phenomenon of the Au nanoparticles can efficiently capture visible light of 520-550nm.

4. A method for preparing the plasma-enhanced magnetic nanocomposite photocatalyst with memory catalytic effect as claimed in claim 1, characterized in that: The following steps are involved: S1, NaYF4:Yb,Tm upconversion nanoparticles were synthesized by hydrothermal method; S2, NaYF4:Yb,Tm@TiO2 core-shell structure prepared by sol-gel method; S3, preparation of NaYF4:Yb,Tm@TiO2 / Fe3O4 nanopowder by calcination method; S4, Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanopowders were prepared by in situ reduction deposition method.

5. The method for preparing a plasma-enhanced magnetic nanocomposite photocatalyst with memory catalytic effect according to claim 4, characterized in that: Step S1 includes the following steps: S101: Sodium hydroxide, oleic acid, and 12 mL of anhydrous ethanol were added to a 50 mL glass beaker and stirred thoroughly to obtain a white viscous liquid. 4.8 mmol of NH₄F was added to the mixed solution and stirred continuously to obtain a clear solution. Subsequently, 1.5 mL of a 0.8 M LnCl₃ solution (Y:Yb:Tm = 79.5:20:0.5) was added and stirred at room temperature for 20 min to form a translucent colloidal solution. S102, transferring the mixed solution obtained in step S101 to a Teflon-lined high-pressure reactor for hydrothermal reaction; after the solution is naturally cooled to room temperature, it is transferred to a sample tube and centrifuged at 4000 rpm for 10 minutes. The sample is washed three times with cyclohexane and ethanol respectively; finally, the powder is dried at 60°C to obtain NaYF4:Yb,Tm upconversion nanoparticle powder.

6. The method for preparing a plasma-enhanced magnetic nanocomposite photocatalyst with memory catalytic effect according to claim 4, characterized in that: Step S2 comprises the following steps: ultrasonically dissolving 1 mol of NaYF4:Yb,Tm in a certain amount of cyclohexane, adding CTAB and 1 ml of NaYF4:Yb,Tm solution to 20 ml of deionized water, and vigorously stirring in a flask. When the solution turns milky white, the system is placed in an 80°C water bath to evaporate the cyclohexane. After the solution becomes clear, it is cooled at room temperature and centrifuged at a speed of 4000 min / r for 5 min to obtain CTAB-modified hydrophilic NaYF4:Yb,Tm; washing the sample with water twice, and then redispersing it in anhydrous ethanol; and fully mixing and stirring the NaYF4:Yb,Tm / CTAB solution and 0.3 mL of ethanol under magnetic stirring. 28wt% ammonia water and 5mL water were added, followed by the slow dropwise addition of 2mol isopropyl titanate isopropanol solution. The above solution was stirred and aged at room temperature for 12h. The sample was collected after centrifugation at 4000r / min, washed twice with ethanol and isopropanol, and then dried at 60°C. Finally, the nanopowder was calcined at 450°C in a muffle furnace for 3h to obtain NaYF4:Yb,Tm@TiO2 nanomaterials.

7. The method for preparing a plasma-enhanced magnetic nanocomposite photocatalyst with memory catalytic effect according to claim 4, characterized in that: The step S3 includes the following steps: weighing 1 g of the core-shell structured NaYF4:Yb,Tm@TiO2 prepared in step S2, adding 10 mg of Fe3O4 powder at a ratio of 1 wt%, and grinding the two in an agate mortar for 10 minutes to ensure thorough mixing; then placing the mixed powder in a muffle furnace, calcining at a constant temperature of 350° C. for 5 hours, and naturally cooling to obtain NaYF4:Yb,Tm@TiO2 / Fe3O4 nanopowder.

8. The method for preparing a plasma-enhanced magnetic nanocomposite photocatalyst with memory catalytic effect according to claim 4, characterized in that: Step S4 includes the following steps: 0.1 g of the NaYF4:Yb,Tm@TiO2 / Fe3O4 nanopowder prepared in step S3 is uniformly dispersed in 100 mL of deionized water, 0.1 g / mL of HAuCl4·3H2O aqueous solution is added under continuous stirring, and the mixture is reacted at 80°C for 15 minutes; then 5 mL of a freshly prepared 0.1 mmol / L trisodium citrate solution is quickly injected, and stirring is continued for 10 minutes; after the above solution is cooled to room temperature, the sample is collected after centrifugation at a speed of 4000 min / r, washed three times with deionized water, and then dried at 60°C to obtain Au-deposited NaYF4:Yb,Tm@TiO2 / Fe3O4 nanomaterial.

9. The method for preparing a plasma-enhanced magnetic nanocomposite photocatalyst with memory catalytic effect according to claims 5 to 8, characterized in that: In step S101, the amount of sodium hydroxide added is 10-15 g, and the amount of oleic acid added is 10-20 ml; In step S102, the hydrothermal reaction temperature is 150-200° C., and the hydrothermal time is 12-16 hours; In step S2, the amount of CTAB added is 0.05-1.5 g, the calcination temperature is 350-600° C., and the calcination time is 3-6 h; In step S3, the calcination temperature is programmed to rise at a heating rate of 20° C. / min, and the calcination time is 4-5 h.

10. Use of the plasma-enhanced magnetic nanocomposite photocatalyst with memory catalytic effect according to any one of claims 1 to 3 in wastewater treatment.